2020
DOI: 10.1371/journal.pntd.0008360
|View full text |Cite
|
Sign up to set email alerts
|

Social marketing interventions for the prevention and control of neglected tropical diseases: A systematic review

Abstract: Background Social marketing is an approach to behavior change that contributes to disease prevention and control. This study aimed to understand how social marketing interventions have addressed neglected tropical diseases (NTDs). It examined the characteristics, breadth of coverage, and outcomes of social marketing interventions focused on the prevention and control of these diseases. Methodology/Principal findings Studies published in any language between January 1971 and April 2017, targeting at least one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 81 publications
(493 reference statements)
0
9
0
2
Order By: Relevance
“…Second, only three published papers examined NTDs (on lymphatic filariasis and scabies) in the Pacific, creating a dearth of qualitative evidence from which to guide implementation of effective NTD control programs in the Pacific region more specifically. Our analysis contributes to the growing body of NTD-related systematic, rapid and scoping reviews with a focus on, for example, social stigma [60]; treatment adherence [61,62]; community understandings of mass drug administration for specific NTDs [63]; the role of nurses, community health workers and community drug distributors in responses to NTDs [64] [65,66]; and innovation in responses to tackling NTDs [67][68][69][70][71][72].…”
Section: Discussionmentioning
confidence: 99%
“…Second, only three published papers examined NTDs (on lymphatic filariasis and scabies) in the Pacific, creating a dearth of qualitative evidence from which to guide implementation of effective NTD control programs in the Pacific region more specifically. Our analysis contributes to the growing body of NTD-related systematic, rapid and scoping reviews with a focus on, for example, social stigma [60]; treatment adherence [61,62]; community understandings of mass drug administration for specific NTDs [63]; the role of nurses, community health workers and community drug distributors in responses to NTDs [64] [65,66]; and innovation in responses to tackling NTDs [67][68][69][70][71][72].…”
Section: Discussionmentioning
confidence: 99%
“…Social marketing is highly effective in encouraging people to engage in proper health behaviors. Various studies reported successful campaigns that used this approach all around the world [ 16 - 20 ] Segmentation of target population are of crucial importance for the effectiveness of inter-ventions.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement in the behaviors, for this group, need to be more attractive. Social marketing can help promoting healthy behaviors of such groups [ 16 - 20 ].…”
Section: Application Of Social Marketing In the Context Of Covid-19mentioning
confidence: 99%
“…Notably, multi-stakeholder partnership leads to achieve successful outcomes of the interventions. Furthermore, the importance of incorporating health education and capacity building for the development of the programmes to prevent communicable disease is highlighted (Aya Pastrana, et. al, 2020).…”
Section: Public Health Complex Interventionmentioning
confidence: 99%